Literature Review: The Contribution Of Decentralization To The Fight Against Corruption In The Era Of The New Public Administration Reform (Case Of Morocco) (Journal of Namibian Studies : History Politics Culture, 2024)
Decentralization and efficiency of public administration are seen as popular tools implemented by governments to ensure transparency globally. This research evaluates the contribution of decentralization to the reduction of corruption in the era of public administration and civil service reform in Morocco. And introduces new guidelines to achieve a higher level of transparency and good governance, and therefore lower levels of corruption.